2017
DOI: 10.3354/meps12017
|View full text |Cite
|
Sign up to set email alerts
|

Subtle but significant segregation in the feeding ecology of sympatric penguins during the critical pre-moult period

Abstract: Niche partitioning plays an important role in minimising interspecific competition for resources. Using carbon and nitrogen stable isotopic analysis of feathers, we investigated how macaroni penguins Eudyptes chrysolophus and eastern rockhopper penguins E. chrysocome filholi breeding at the Prince Edward Islands partition the marine environment during the critical pre-moult period over 5 consecutive years (2011 to 2015). Both species consistently foraged immediately south of the Antarctic Polar Front, with mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Marked sex-dependent differences in the choice of foraging habitat were reported during the pre-moult stage in Macaroni penguins from Crozet and Kerguelen [ 43 ] as well as Rockhopper penguins from Marion Island [ 44 ]. However, stable isotope analyses in Southern Rockhopper penguins from the Falkland Islands (Malvinas) showed that during the pre-moult stage both sexes forage on the same trophic levels indicating common foraging grounds [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marked sex-dependent differences in the choice of foraging habitat were reported during the pre-moult stage in Macaroni penguins from Crozet and Kerguelen [ 43 ] as well as Rockhopper penguins from Marion Island [ 44 ]. However, stable isotope analyses in Southern Rockhopper penguins from the Falkland Islands (Malvinas) showed that during the pre-moult stage both sexes forage on the same trophic levels indicating common foraging grounds [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other nine species exhibited intermediate δ 13 C memb , suggesting that during egg formation they gathered nutrients from intermediate waters between the Subtropical Front and Antarctic Polar Front as suggested by tracking data for some of them (Reisinger et al 2018). Wandering albatross females obtained their nutrients at one trophic level above grey-headed albatrosses, and king penguins at a higher trophic level than the two crested penguins, showing similar trophic segregation to the chick-rearing period (Adams and Brown 1989, Hunter and Klages 1989, Cooper et al 1992, Whitehead et al 2017; although fasting by penguins during the last stage of oogenesis (Ancel et al 2013) may influence the isotopic ratios of egg components. We did not explicitly calculate trophic levels in our study but captive studies have estimated trophic discrimination factors between food and egg membrane to be between 3 and 4‰ in seabirds (Polito et al 2009).…”
Section: Isotopic Partitioning By Feedingmentioning
confidence: 78%
“…We did not explicitly calculate trophic levels in our study but captive studies have estimated trophic discrimination factors between food and egg membrane to be between 3 and 4‰ in seabirds (Polito et al 2009). Wandering albatross females obtained their nutrients at one trophic level above grey-headed albatrosses, and king penguins at a higher trophic level than the two crested penguins, showing similar trophic segregation to the chick-rearing period (Adams and Brown 1989, Hunter and Klages 1989, Cooper et al 1992, Whitehead et al 2017; although fasting by penguins during the last stage of oogenesis (Ancel et al 2013) may influence the isotopic ratios of egg components. Interestingly, lesser sheathbills are often found around the colonies of crested penguins either stealing food from the penguins or scavenging from carcasses.…”
Section: Isotopic Partitioning By Feedingmentioning
confidence: 96%
“…Marked sex-dependent differences in the choice of foraging habitat were reported during the premoult stage in Macaroni penguins from Crozet and Kerguelen [41] as well as Rockhopper penguins from Marion Island [42]. However, stable isotope analyses in Southern Rockhopper penguins from the Falkland Islands (Malvinas) showed that during the pre-moult stage both sexes forage on the same trophic levels indicating common foraging grounds [43].…”
Section: Spatial Segregation Of Trip Destinationsmentioning
confidence: 99%